Development and Early Implementation of a Public Communication Campaign to Help Adults to Support Children and Adolescents to Cope With Coronavirus-Related Emotions: A Community Case Study - Raccanello, Daniela; Vicentini, Giada; Rocca, Emmanuela; Barnaba, Veronica; Hall, Rob; Burro, Roberto (Frontiers in Psychology, 2020)
Epidemics and pandemics can traumatically impact the emotional wellbeing of adults, children, and adolescents in diverse ways. This impact can be reduced by applying a range of evidence-based coping strategies. Based on previous research, we created a pamphlet-based communication campaign designed to assist adults to provide support for young people confronted with emotional distress associated with the pandemic caused by the novel coronavirus [severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)] and the related disease [coronavirus disease (COVID-19)] in 2020. We developed a pamphlet describing the common emotions children and adolescents report feeling in the face of disasters and the coping strategies that have proven effective in mitigating them. The target population was adults who interact with children and adolescents in both formal and informal settings. The pamphlet included basic information on this specific emergency, emotions that might be commonly experienced, and coping strategies for dealing with negative emotions. The aim of this paper is to describe the planning, development, and implementation of the campaign. First, we monitored how the media gave visibility to the campaign during the 40 days following the release of the pamphlet: it potentially reached a large audience at a national and international level through at least 216 media channels included the HEMOT® (Helmet for EMOTions) website. Second, Google Analytics™ data from the HEMOT® website enabled us to examine the characteristics of the visitors to the website and the behavior of those who viewed the pamphlet. More than 6,000 visitors, most from Europe followed by the Americas, visited the website in the first 40 days after the pamphlet publication. The webpage including the pamphlet obtained over 6,200 views, most directly or via other websites. A cluster analysis suggested that the access to the webpage did not mirror the trend concerning the new cases of COVID-19 in Italy (which increased during the central phase of the campaign) or worldwide (which continued to increase across the 40 days). Third, data gathered with a convenience sample of adults who had consulted the pamphlet provided a perspective on the comprehensibility of the messages conveyed by the pamphlet and on the utility for children and adolescents. The process we have demonstrated in this example could be replicated in different communities and settings to respond to the spread of the COVID-19 or to respond to other widespread or more localized disasters.